Structural Element Approach in Model Development of Federal Land Development Authority (FELDA) - Hairol Anuar Hj Mak Din,; Nor Azlili Hassan,; Mansor Mohd Noor, (Journal of Social Transformation and Regional Development, 2019)
The socio-economic development planning of a country depends largely on the land owned assets. The ability to optimize the land management is effectively able to benefit various parties and the country as well. Malaysia is an example of a successful country in dynamically managing the land usage through the establishment of the Federal Land Development Authority (FELDA). During the research period, FELDA was found to have been transformed as one of the strategic statutory bodies in which the institution is not only able to generate its own income, but also to organize the structured programs to successfully develop the human capital. This article is a sub topic from a study on Felda by focusing on the role of structural factor which aims to analyse the level of satisfaction with the basic facilities in FELDA Land Plans and the level of satisfaction with social development. The methodology employed in this study is purposive sampling methods and multi-stages which comprising of the FELDA settlers from two states namely, Pahang and Johor. A total of 1,501 respondents were involved in this quantitative study. This study discusses dimensions of the level of satisfaction on the basic facilities in FELDA Land Plans and level of satisfaction on the social development. The findings indicated that the level of satisfactions for the basic facilities and social developmenet are 90% and 80%.